ANALISIS TEKNIK PERMAINAN BIOLA PADA KARYA ZIGEUNERWEISEN DARI PABLO MARTIN MELITON DE SARASATE Y NAVAZCUES OP.20 - Iskandar, Farih Ibnu Iskandar (Program Studi Pendidikan Musik, 2022)
Abstract: This research using a qualitative research methods with a musicological approach. This research was conducted in February – June 2021, at the writer's place, located at Jl. Al-Nur RT 01/ RW 06 No.70 Kel. Pabuaran, Kec. Cibinong, Kab. Bogor, West Java. The Data collection is done by using Literature review, Documentation Study, Observation and Interview. Other than that, the data analysis techniques that the writer used for the research are Data Reduction, Codeing, Data Presentation, and Drawing Conclusions. In testing the validity of the data, the writer using the Triangulation Technique.The result of this study is the writer find out that the work of Zigeunerweisen (Gypsi Airs) Pablo de`Sarasate Op.20 has 1 movement consisting of 4 parts, there are Moderato, Lento, Un Peu Plus Lento (in C minor scales), and Allegro molto Vivace (in C minor scales). a minor). The techniques contained in these work are including Legato, Sull, Spiccato, Flying Staccato, Multiple Stops, Ricochet, Pizzicato left and right hand, Portamento and Glissando, natural and artificial harmonics. Keywords: Technique, Violin, Zigeunerweisen, Pablo de`Sarasate Op.20